(untitled) (PYC Nepal Journal of Management, 2015)
Entrepreneurship is the engine for social and economic growth of any society. It drives people toward wealth and job creation which leads to better lives for people in the society. There has been growing interest in entrepreneurship research recently. This paper attempted to assess the impact of caste/ethnicity in Nepalese society. This was viewed as essential in a country in which more than 125 ethnic communities are found. The findings show that caste/ethnicity has some impact in people to become entrepreneurship but it was not strongly substantiated by statistical tests. In fact, it was found that people from those communities which would be considered as less entrepreneurial were involved in entrepreneurship in Nepal indicating the changing social trend in which people from all the communities are involved in entrepreneurial activities. This can be viewed as a positive sign toward new value system of Nepali people in which one’s caste/ethnicity plays less role in the choice of a profession.